KUBAH NOVEL BY AHMAD TOHARI IN PROPHETIC PERSPECTIVE - Teguh Prakoso (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2020)
Through this article, the researcher wants to describe the story structure of Kubah’s novel by Ahmad Tohari from the perspective of Kuntowijoyo’s Prophetic Ethics. In this novel, the author who was born in Tinggarjaya managed to package how religion, in this case, Islam, is a guide to social life. The message, for example, was conveyed through his transformation into Haji Bakir and Karman in the Kubah novel. The method used in this article is structurally based on the Kuntowijoyo Prophetic Notice. In the story structure, the dome set in a rural social setting was arranged harmoniously by Tohari and integrated with the G30 S/PKI conflict that occurred Pegaten Village. The figure of Haji Bakir is presented to enlighten how Islam is rahmatanlilalaamin. What Tohari initiated was in line with Kuntowijoyo’s thoughts about amarmakruf, nahimunkar, and tu’minunnabillah. The harmonization produced a more interesting analysis because of Tohari’s background in representing the nahdliyin community which was combined with Kuntowijoyo’s prophetic notice as moderate Islam. The results showed that the events told in Kubah novel have described how the attitudes and behaviors of the community life on a religious basis. Through figures Karman, Mami, Haji Bakir, Gethek Caste, and a series of other figures. How to love fellow humans with the provision of Islam as ralmatanilalaamin has been shown. This is the essence of the application of Kuntowijoyo’s prophetic perspective in the Kubah Novel.